Analisis Kelayakan Bisnsi Dari Inovasi Lemari Pakaian Kayu Dengan Meja Belajar - Fernando Agusto P; Agustian Suseno (Peneliti.net, 2022)
In today's life the term practical is one of the terms favored by everyone. Because it can make a job easier or in one item you can do two different things in the same place. As is the case with the wardrobe innovation with a study table on the side of the cupboard, this product will make it easier for office workers who have problems. money in buying a work desk and wardrobe. Wardrobe is one of the supporting facilities for storing clean clothes and a study table is one means to facilitate users in the learning process. With the rapid development of society regarding the use of wardrobes and the increasing number of workers who have to work from home due to the COVID-19 pandemic. With this incident used by the craftsmen to try an innovation to meet all the needs of the community by combining two products, namely a cupboard with a study table. Using the QFD (Quality Function Deployment) method can make it easier for business people to monitor businesses around them.